Application of Autodock Vina program version 1.1.2 for Exploring Indonesian Phytochemicals as an Activator of Adenosine Monophosphate-Activated Protein Kinase - Farchan Azzumar; Dono Indarto; Balgis . (Nexus Kedokteran Translasional, 2015)
Background: Increased activity of Adenosine Monophosphate-Activated Protein Kinase (AMPK) can inhibit cell growth and biosynthetic pathwaysin some cancer cells. Recently, several endogenous ligands have been identified to activate AMPK including Adenosine Monophosphate (AMP).Virtual screening is one of the recent technique, which is used for drug discoveries.Therefore the aim of this study was to identify active compounds of Indonesian herbal plants that activate AMPK by using molecular docking. Methods: Samples used in this study wereall of active compounds which were derived from Indonesian herbal plantsand had three-dimensional structures. Molecular docking was performed by using AutodockVina version 1.1.2 to evaluate interaction between AMPK and active compounds. The AMP structure obtained from protein data bank (www.rcsb.org/pdb)was used as a molecule standard of AMPK interaction. Docking score indicated affinity of molecule interaction and was determined in Cal/mol. To visualize docking results that fit to the AMPK molecule, chimera software version 1.9 was used. Results: Curcumin has docking scores as same as docking score of AMP (-7.5 Cal/mol) and has hydrogen bound in ? subunit of AMPK (Thr86, Thr88, and Arg117). Conclusions: Curcumin might be an activator of AMPK. Another molecular docking which has a flexible substrate-enzyme algorithm is required for confirming the docking result. Keywords: AMPK, Herbal plant, Molecular Docking.